Development of powdered kamias (Averrhoa bilimbi Linn.) as soup base - Santos Rachel David
The study involved the development of a cabinet-dehydrated powdered kamias to be incorporated in a soup base formulation. Phase I involved the selection of the best stage of maturity of the kamias raw material as evaluated in terms of size, color, texture, moisture content, soluble solids, titrable acidity and pH. Results showed that the sample group with the best stage of maturity had a moisture content of 92.87%; %SS of 4.33; %TA of 1.3 and a pH of 2.03. Sulfiting and 60-second steaming as pretreatments gave the most acceptable effect on the dried kamias sample as determined in Phase II. The dried sample was powdered and characterized to have a moisture content of 11.68%; pH of 2.0; a TA of 2.87% and a percentage yield of 5.64. Microbiological examination of the kamias powder showed an estimated Total Plate Count of 10 cfu/gram and a negative result for yeasts and molds. Phase III dealt with the determination of the most acceptable formulation of the kamias soup base. Among the three formulations that were prepared and subjected to a sensory panel for flavor evaluation, formulation T54 was chosen as the best one. The kamias soup base was found out to be 57% by weight kamias powder. The panelists gave the soup base a general acceptability of "like very much" and described the product as having a characteristic kamias flavor with the right combination of sourness and saltiness. The final moisture content of the kamias soup base was chosen as the best one. The kamias soup base was found out to be 57% by weight kamias powder. The panelists gave the soup base a general acceptability of "like every much: and described the product as having a characteristic kamias flavor with the right combination of sourness and saltiness. The final moisture content of the kamias soup base was 6.8%.